Meats - Cottrell, Jennie Pearl (My University, 1904)
Introduction: Meat has been defined as the flesh of animals used for food. It is probably one or the oldest forms of food known to man. In his savage state it was his chief food together with the simple herbs of field and forest. In the early history of England it was regarded as the principal and essential dish at a meal; especially was this true of feasts and banquets. This is shown by the frequency with which it is mentioned in ancient ballads. One writer has said that the feast songs were always of meat and points to the fact that it was the boar's head which was decked with holly and brought to the table with so much ceremony and not the potato. The importance it held in the bill of fare is illustrated in Dean Swift's description of a mid-day dinner of Old England, which is as follows:- Oysters, Sir Lyon of beef, a shoulder of veal, fish dressed -with claret, Tongue, pigeons, cowcumbers, fritters, almond pudding, soup. After the soup was removed it was followed by a venison pastry, black pudding, hare and goose." Truly the partakers of this meal must have felt little need for further refreshment. Although at the present time meat does not occupy as important a place in the diet as formerly, still the majority of us feel that at least one meal of the day should have a fair allotment of this food and that it is one of the staple articles of diet. The source as given in the definition is seen to be the lower animals. The kinds of meat, are named for the animal from which obtained. Smith in his book on "Foods" divides animal foods into flesh, fish, and fowl, and includes under flesh what is known as butcher's meat or beef, pork, mutton, lamb, and veal. Hutchinson classes meats proper under butcher's meat poultry, game and "offal." Under the heading. butcher's meat we have…
Citation: Cottrell, Jennie Pearl. Meats. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Meat; Cooking; Cooking Meat; Types of Meat; Theses